PATHOPHYSIOLOGY AND FUNCTIONS OF THE KIDNEYS: AN INTEGRATIVE OVERVIEW - Turaev Umar Rahimovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The kidneys are essential for maintaining internal homeostasis through their roles in filtration, reabsorption, secretion, and hormone production. Disruption in kidney function leads to a wide range of systemic complications. This review discusses the primary physiological functions of the kidneys and explores the underlying pathophysiological mechanisms in common renal diseases such as acute kidney injury (AKI), chronic kidney disease (CKD), and glomerulonephritis.